Preparation And Properties Of Impact Modified Poly(Lactic Acid)/Kenaf Fiber Composites - Ali Ghaleb, Zaid Aws (2011)
Preparation And Properties Of Impact Modified Poly(Lactic Acid)/Kenaf Fiber Composites